Antioxidant depletion of HDPE geomembrane with sand protection layer. Issue 2 (April 2013) - Rowe, R.K.; Abdelaal, F.B.; Brachman, R.W.I.
Abstract : ABSTRACT: The performance of a 1.5 mm thick high-density polyethylene geomembrane (GMB) in simulated municipal solid waste landfill liners is presented. Accelerated ageing experiments were conducted in geosynthetic liner longevity simulators that allow simulation of field conditions including elevated temperatures, overburden pressure, leachate circulation and composite liner exposure conditions. A 150 mm sand protection layer was used between a gravel drainage layer and an underlying GMB liner. A comparison between the results obtained for this sand protection layer and those obtained for a 580 g/m 2 geotextile protection layer is presented in terms of both antioxidant depletion and tensile strains. The antioxidant depletion stage for the GMB with the sand protection layer was predicted to be around 500 and 9 years at 20°C and 60°C, respectively. The antioxidant depletion stage with a sand protection layer was longer than that with geotextile protection by a factor of 1.6 for the same GMB, leachate and test boundary conditions. A comparison between the tensile strains induced in the GMB with sand and geotextile protection layers shows that the long-term tensile strains in the GMB with a sand protection layer were substantially lower than those for the GMB with a 580 g/m 2 geotextile protection layer.